Calibration‐free parallel transmission of the cervical, thoracic, and lumbar spinal cord at 7T - Aigner, Christoph S.; Sánchez Alarcon, Manuel F.; D'Astous, Alexandre; Alonso‐Ortiz, Eva; Cohen‐Adad, Julien; Schmitter, Sebastian (Magnetic resonance in medicine, 2024)
Purpose To address the limitations of spinal cord imaging at ultra‐high field (UHF) due to time‐consuming parallel transmit (pTx) adjustments. This study introduces calibration‐free offline computed universal shim modes that can be applied seamlessly for different pTx RF coils and spinal cord target regions, substantially enhancing spinal cord imaging efficiency at UHF. Methods A library of channel‐wise relative B1+$$ B_1^{+} $$ maps for the cervical spinal cord (six datasets) and thoracic and lumbar spinal cord (nine datasets) was constructed to optimize transmit homogeneity and efficiency for these regions. A tailored B0 shim was optimized for the cervical spine to enhance spatial magnetic field homogeneity further. The performance of the universal shims was validated using absolute saturation based B1+$$ B_1^{+} $$ mapping and high‐resolution 2D and 3D multi‐echo gradient‐recalled echo (GRE) data to assess the image quality. Results The proposed universal shims demonstrated a 50% improvement in B1+$$ B_1^{+} $$ efficiency compared to the default (zero phase) shim mode. B1+$$ B_1^{+} $$ homogeneity was also improved by 20%. The optimized universal shims achieved performance comparable to subject‐specific pTx adjustments, while eliminating the need for lengthy pTx calibration times, saving about 10 min per experiment. Conclusion The development of universal shims represents a significant advance by eliminating time‐consuming subject‐specific pTx adjustments. This approach is expected to make UHF spinal cord imaging more accessible and user‐friendly, particularly for non‐pTx experts.